2022
DOI: 10.1590/2175-8239-jbn-2021-0089
|View full text |Cite
|
Sign up to set email alerts
|

NOS3 gene intron 4 a/b polymorphism is associated with ESRD in autosomal dominant polycystic kidney disease patients

Abstract: Introduction: Endothelial nitric oxide synthase (eNOS) genes have been implicated in renal hemodynamics as potent regulators of vascular tone and blood pressure. It has been linked to a reduction in plasma nitric oxide levels. Several studies have recently been conducted to investigate the role of NOS3 gene polymorphisms and end-stage renal disease (ESRD). However, the results are still unclear and the mechanisms are not fully defined. As a result, we conducted a meta-analysis to examine the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The ACP2 protein was included in a prognostic model of DKD including 35 DKD patients with good and 19 with poor prognosis [ 68 ]. On the other hand, associations in ATP5G1 , the ATP Synthase Membrane Subunit C Locus 1 represents one of the novel findings in our study [ 62 ].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The ACP2 protein was included in a prognostic model of DKD including 35 DKD patients with good and 19 with poor prognosis [ 68 ]. On the other hand, associations in ATP5G1 , the ATP Synthase Membrane Subunit C Locus 1 represents one of the novel findings in our study [ 62 ].…”
Section: Discussionmentioning
confidence: 71%
“…NOS3 encodes the nitric oxide synthase 3, involved in endothelin pathways and the EGF/EGFR signalling pathway, whose inhibition protects against the development of DKD [ 162 ]. There is a clear link between NOS3 gene variation and ESKD [ 62 , 63 ], CKD [ 64 ] and CKD progression [ 65 ]. A recent meta-analysis of 13 studies found that two NOS3 gene polymorphisms (rs1799983, R2 = 0.189 with rs3918226 and the intron 4 VNTR a/b polymorphism) significantly increased ESKD risk in autosomal dominant polycystic kidney disease (ADPKD) patients [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the presence of the 4a allele may be related to kidney dysfunction and other pathological conditions. Thus, there are data on the association of the rs61722009 variant of the NOS3 gene with the progression of nephropathy in patients with diabetes and Fabry disease, an increased risk of end-stage renal failure in patients with autosomal polycystic kidney disease [ 15 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…eNOS genes have been implicated in renal hemodynamics as potent regulators of vascular tone. 46 In this study, to understand the multiple, overlapping factors that affect renal hemodynamics, ultrasonography was used to provide a real-time and dynamic assessment of renal cortex microvascular perfusion and hemodynamic characteristics. 47 Several studies have shown that progressive exacerbation of DN is accompanied by a decrease in renal artery blood flow velocity and an increase in renal artery resistance.…”
Section: Discussionmentioning
confidence: 99%